Facilitating literature searches for work based learning students using an action research approach. Issue 4 (1st October 2020) - Talbot, Jon; Bennett, Lee
ABSTRACT: This paper describes an action research project in a university to identify the requirements of Work-Based Learning (WBL) students in respect of literature searches for practice enquiries and outlines measures subsequently taken to improve student support. The study confirms previous research that WBL students need to consult a wide variety of source material and not just academic texts. Students report uncertainty in using non-academic sources and difficulties searching. As a result, academic practices have been adapted to provide more consistent, comprehensive support. These include the production of online resources and modified practices by tutors and librarians. In line with the action research approach, practices are monitored on an ongoing basis to ensure their continuing relevance.